2011
DOI: 10.1002/jrs.2872
|View full text |Cite
|
Sign up to set email alerts
|

Historical organic dyes: a surface‐enhanced Raman scattering (SERS) spectral database on Ag Lee–Meisel colloids aggregated by NaClO4

Abstract: In the present study, several natural organic dyes used in antiquity, especially in textile dyeing, were analysed by surfaceenhanced Raman scattering (SERS) spectroscopy, in order to build a wide database that could integrate the data previously published in the literature. In particular, we reported for the first time the SERS spectra of 11 dyes: dragon's blood, sandalwood, annatto, safflower yellow and red, old fustic, gamboge, catechu, kamala, aloe and sap green. Silver colloids (Ag colloids) prepared accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
99
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 60 publications
(109 reference statements)
16
99
1
Order By: Relevance
“…In the last decade, the successful application of the high sensitive surface enhanced (resonance) Raman spectroscopy [SE(R)RS] for the detection of organic dyes in works of art has strongly improved the possibility of identifying fluorescent organic dyes according to minimal invasive [10][11][12][13][14] and microdestructive approaches [15][16][17]. Up to the present, the majority of the developed SERS procedures dealt mainly with the detection of red and yellow dyes [15][16][17][18][19][20][21][22][23][24][25][26], whereas only a few works have investigated the characterization of indigoids by means of SERS/SERRS. One of the main problems is that indigo is insoluble in the aqueous silver colloid dispersion and it must be treated by specific solvents prior to SERS analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the successful application of the high sensitive surface enhanced (resonance) Raman spectroscopy [SE(R)RS] for the detection of organic dyes in works of art has strongly improved the possibility of identifying fluorescent organic dyes according to minimal invasive [10][11][12][13][14] and microdestructive approaches [15][16][17]. Up to the present, the majority of the developed SERS procedures dealt mainly with the detection of red and yellow dyes [15][16][17][18][19][20][21][22][23][24][25][26], whereas only a few works have investigated the characterization of indigoids by means of SERS/SERRS. One of the main problems is that indigo is insoluble in the aqueous silver colloid dispersion and it must be treated by specific solvents prior to SERS analyses.…”
Section: Introductionmentioning
confidence: 99%
“…SERS is a popular method in a dye analysis especially in the field of art conservation. there is a few reports with the application of this technique for the analysis of natural dyes in textiles [31][32][33][34]. the use of SERS to the in situ analyses of natural samples is still discussed and developed [35].…”
Section: Vibrational Spectroscopy Techniquesmentioning
confidence: 98%
“…Particle size, shape, and resulting plasmonic properties can be fine-tuned by suitable choice of the metal, reducing agent and stabilizer, chemicals concentration, addition rate, and temperature. In addition to testing alternative reducing agents, such as hydroxylamine (Leopold and Lendl 2003) and borohydride (Creighton et al 1979), research groups all over the world have evaluated how different aggregants-including potassium nitrate (Cañamares et al 2004), poly-L-lysine (Shadi et al 2004), sodium chloride (Cañamares et al 2008b) and perchlorate (Bruni et al 2011a)-may promote the association of nanoparticles in clusters of various dimensions, where localized regions of intense electromagnetic fields, the so-called hot spots, are responsible for a giant enhancement of the Raman signal (Ringe et al 2013). An alternative to Lee-Meisel colloids involves a synthetic protocol based on the glucose-assisted reduction of silver sulfate in the presence of sodium citrate as a capping agent (Leona 2009).…”
Section: Colloidal Nanoparticlesmentioning
confidence: 99%
“…The molecule of interest, alizarin, is adsorbed onto an Ag nanoparticle substrate. The substrate is then irradiated with laser light (green), and the enhanced Raman scattering (red) is detected Geiman et al 2009;Chang et al 2009;Xie et al 2012;Bruni et al 2011a;Mayhew et al 2013;Benedetti et al 2014;Greeneltch et al 2012;Doherty et al 2014;Cañamares and Lombardi 2015;Zaffino et al 2015) can also be found in the literature. In addition to providing valuable reference spectra for identification purposes, these works have explored aspects such as the influence of pH on the resulting spectral patterns, and the binding geometry and relative orientation of the molecules examined with respect to the metal surface.…”
Section: Introductionmentioning
confidence: 99%